PUFA levels in erythrocyte membrane phospholipids are differentially associated with colorectal adenoma risk. Issue 11 (29th June 2017) - Rifkin, Samara B.; Shrubsole, Martha J.; Cai, Qiuyin; Smalley, Walter E.; Ness, Reid M.; Swift, Larry L.; Zheng, Wei; Murff, Harvey J.
Abstract: Dietary intake of PUFA has been associated with colorectal neoplasm risk; however, results from observational studies have been inconsistent. Most prior studies have utilised self-reported dietary measures to assess fatty acid exposure which might be more susceptible to measurement error and biases compared with biomarkers. The purpose of this study was to determine whether erythrocyte phospholipid membrane PUFA percentages are associated with colorectal adenoma risk. We included data from 904 adenoma cases and 835 polyp-free controls who participated in the Tennessee Colorectal Polyp Study, a large colonoscopy-based case–control study. Erythrocyte membrane PUFA percentages were measured using GC. Conditional logistic regression was used to calculate adjusted OR for risk of colorectal adenomas with erythrocyte membrane PUFA. Higher erythrocyte membrane percentages of arachidonic acid was associated with an increased risk of colorectal adenomas (adjusted OR 1·66; 95 % CI 1·05, 2·62, P trend =0·02) comparing the highest tertile to the lowest tertile. The effect size for arachidonic acid was more pronounced when restricting the analysis to advanced adenomas only. Higher erythrocyte membrane EPA percentages were associated with a trend towards a reduced risk of advanced colorectal adenomas ( P trend =0·05). Erythrocyte membrane arachidonic acid percentages are associated with an increased risk of colorectal adenomas.